PENDIDIKAN KESEHATAN TENTANG ANTENATAL CARE DI MASA PANDEMI COVID 19 - Tutik Ekasari (STIKES NGUDIA HUSADA MADURA, 2022)
Indonesia is one of the countries affected by the Corona Virus Disease-19 (Covid-19) pandemic with a fluctuating number of confirmed cases of Covid-19 (new cases). The provision of maternal services during the pandemic needs to be a concern to avoid an increase in maternal morbidity and mortality, especially when there are restrictions on maternal health services. This can be a factor causing anxiety that occurs in pregnant women. The purpose of this PKM is to increase awareness of pregnant women to check their pregnancy and the output targets to be achieved are and articles. This Community Service method is health education to the community about antenatal care during the covid 19 pandemic. The participants are posyandu cadres, pregnant women and women of childbearing age as many as 30 people at the Posyandu Dusun Mudinan II Pajurangan Village, Gending District, Probolinggo Regency. The results of the PKM activity are that participants understand and are able to explain again about antenatal care during the Covid 19 pandemic and have reduced their worries about getting their pregnancy checked. Keywords: Antenatal care, Covid 19 pandemic, Visits